Function and Use of Language in Linguistic Landscape Signs at Jakarta Train Station - Andreana, Chesa; Rofiq, Zainur (Inspiring: English Education Journal, 2024)
This research analyzes the function and use of language in Linguistic Landscape signs at three train stations in Jakarta, namely Gambir station, Manggarai station, and Dukuh Atas BNI MRT station. This research examines how Linguistic Landscape signs affect passenger accessibility and comfort. This research uses a qualitative descriptive method, and data is collected through field observations, photo documentation and passenger interviews. Then, the data analysis technique uses the Miles and Huberman (2019) technique, data reduction, data display, and verification. The results of this research show that most of the signs at the three stations are bilingual signs in Indonesian-English, followed by monolingual signs in English and Indonesian. The Linguistic Landscape signs at this station have proven effective in providing information that is easy to understand and easily accessible to local and foreign passengers. These signs also increase accessibility and comfort for passengers at the station. This research contributes to understanding the function and use of language in the Linguistic Landscape of public spaces, especially at train stations.